Motivation and Satisfaction of Arabic Education Students of UIN Maulana Malik Ibrahim Malang in Accessing Arabic Content on Instagram - Maryam, Shovi; Sutaman; Huda, Miftahul (Institut Agama Islam Negeri Curup, 2025)
This study aimed to examine the motivations and satisfaction of Arabic Education students in accessing Arabic content on Instagram by applying the Uses and Gratifications Theory (UGT). While the integration of social media into language learning has received considerable attention, particularly in informal and self-directed settings, limited research has specifically explored students’ motivations and levels of satisfaction in this context. To address this gap, a quantitative approach was adopted, involving 144 randomly selected students. Data were collected through a questionnaire designed to assess the discrepancy between gratification sought and gratification obtained across five dimensions: academic, informational, personal identity, social interaction, and entertainment. The instrument was validated by experts, and its validity and reliability were tested using the Pearson correlation with the bivariate method in SPSS. The results revealed that students were most motivated and satisfied in the academic, informational, and personal identity dimensions. Conversely, the dimensions of social interaction and entertainment did not yield a satisfactory experience. The highest level of motivation and satisfaction was attributed to Instagram’s role in enhancing vocabulary acquisition, whereas the lowest level of gratification was associated with creating Arabic content on the platform. Gender-based differences also emerged: male students reported higher motivation and satisfaction in vocabulary development, increased self-confidence, and improved listening skills, while female students showed greater motivation and satisfaction in vocabulary acquisition, grammar mastery, and reading proficiency. These results contribute theoretically by extending the application of UGT to Arabic language learning through social media. They also offer practical implications for integrating Instagram into instructional strategies and highlight policy-level considerations for acknowledging digital platforms as valid tools in formal education.